Mechanical recycling of acrylonitrile-butadiene-styrene copolymer and high impact polystyrene from waste electrical and electronic equipment to comply with the circular economy - Teixeira, Flávia da Silva Müller; Peres, Augusto Cesar de Carvalho; Pacheco, Elen Beatriz Acordi Vasques (Frontiers in Sustainability, 2023)
Acrylonitrile-butadiene-styrene copolymer (ABS) and high impact polystyrene (HIPS) are plastics typically found in waste electrical and electronic equipment (WEEE or e-waste). As such, recycling is a beneficial method for reintroducing polymeric materials from electrical and electronic equipment to the same production cycle. This study aimed to investigate mechanical recycling of ABS and HIPS from WEEE reprocessed six times, totaling 24 cycles. Reprocessing was performed by extrusion and test specimens were obtained by injection. The technical aspects assessed before and after reprocessing were mechanical properties (tensile, flexural and impact strength), thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR) and melt flow index (MFI), compared with those of reprocessed virgin polymeric materials. The environmental aspect was evaluated by monitoring energy consumption and solid waste generation during each reprocessing cycle. Average energy consumption per extrusion and injection cycle was 0.7 and 2.0 kW/kg, respectively. There was a 30% increase in MFI from the first to sixth reprocessing cycle for virgin HIPS (5.5 g/10min in 200oC and 5kg), the largest among the polymers. The values for virgin ABS (6.0 g/10min in 200oC and 5kg) and ABS and HIPS from WEE increased by 11-15% from the first to sixth cycle. Impact strength was affected from the second reprocessing cycle onwards for ABS e-waste (14% decrease) and in the fifth cycle (16% decrease) for HIPS e-waste. The thermal, tensile and flexural properties of the virgin and post-consumer materials remained almost unchanged as the number of reprocessing cycles increased, indicating that these materials have the potential and properties for reintroduction into the same production cycle.